A Brief Analysis of the Suggestions on Teaching and Student Management in Colleges and Universities Based on Computer Network. Issue 2 (May 2021) - Yang, Wenhua
Abstract: The popularization and even wide use of computer network not only in large enterprises and institutions, but also in other large gathering units and even ordinary individual users. When the convenience and value that the network can provide into colleges and universities, it will bring wonderful reactions to college managers and students [1]. In the face of the unpredictable situation of the results, how to deal with the educational administration and student management based on computer network technology in colleges and universities will become the focus of this paper, and put forward some suggestions.